Noticias de España en las Memorias de Graciliano Ramos - Vieira, Elisa Maria Amorim (2016)
In different passages of Memórias do Cárcere (1953), Graciliano Ramos refers to current events in Spain, relating what happens there with the political situation in Brazil under the dictatorship of Getúlio Vargas. For the enemies of the Brazilian dictatorial regime, the victory of the Spanish Republic in the Civil War represented also the possibility of democracy in their country. This being so, the news coming from Spain are accompanied with enthusiasm by Graciliano Ramos and his fellow prisoners, although local newspapers reflect the Vargas government’s official view, which was in favor of the military uprising led by General Franco. The proposal of this work is, therefore, to analyze the images of Spain and the anti-fascist struggle in this country presented in the work of a Brazilian writer.